Long-term effects of orchard soil management practices on growth, yield and fruit quality of apple (Malus domestica) - KUMAR, JAYANT; REHALIA, A S; RANA, S S; VERMA, H S (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during 1987-95 at Bajaura to study the effect of 5 orchard soil management practices, viz herbicide plus mulching with hay,herbicide, mulching with hay, mulching with white netted polythene and clean cultivation on growth, yield and fruit quality of ’Starking Delicious’ apple (Malus domestica Borich.) grafted on M7 rootstock. The highest trunk girth (55.8 cm), shoot length (46.6 cm) and fruit yield (89.4 kg/tree) was observed with herbicide plus mulching with hay followed by herbicide alone. The lowest trunk girth (52.4 cm), shoot length (32.8 cm) and fruit yield (66.6 kg/tree) was recorded with clean cultivation. The treatment herbicide plus mulching with hay resulted in the highest fruit length (7.20 cm), fruit breadth (7.48 cm) and fruit weight (260.4 g) followed by mulching with hay. The lowest fruit length (6.78 cm), fruit breadth (6.97 cm) arid fruit weight (232.6 g) was observed with clean cultivation. However, the clean cultivation resulted in the highest total soluble solids (15.1 O S). Other quality traits were not influenced. The treatment herbicide plus mulching with hay Can be recommended for apple orchards.